2018
DOI: 10.18632/oncotarget.25418
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aldosterone-producing cell clusters on diagnostic discrepancies in primary aldosteronism

Abstract: Adrenocorticotropic hormone (ACTH) stimulation is recommended in adrenal vein sampling (AVS) for primary aldosteronism (PA) to improve the AVS success rate. However, this method can confound the subtype diagnosis. Gene mutations or pathological characteristics may be related to lateralization by AVS. This study aimed to compare the rate of diagnostic discrepancy by AVS pre- versus post-ACTH stimulation and to investigate the relationship between this discrepancy and findings from immunohistochemical and geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Recent findings have established that the expression of aldosterone synthase is heterogeneous, i.e. its expression is variable, depending for instance on the underlying molecular derangement, and that aldosterone-producing cell clusters (APCCs) in the zona glomerulosa of the adrenal cortex express high levels of aldosterone synthase 20 , 21 . Frozen section autoradiography performed with [ 18 F]CETO, with or without metomidate as a blocking agent, showed that the binding was specific to adrenocortical adenomas (APA and CPA) and adrenocortical carcinomas but not to pheochromocytomas, which showed only unspecific background uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have established that the expression of aldosterone synthase is heterogeneous, i.e. its expression is variable, depending for instance on the underlying molecular derangement, and that aldosterone-producing cell clusters (APCCs) in the zona glomerulosa of the adrenal cortex express high levels of aldosterone synthase 20 , 21 . Frozen section autoradiography performed with [ 18 F]CETO, with or without metomidate as a blocking agent, showed that the binding was specific to adrenocortical adenomas (APA and CPA) and adrenocortical carcinomas but not to pheochromocytomas, which showed only unspecific background uptake.…”
Section: Discussionmentioning
confidence: 99%
“…In pre-adrenocorticotropic hormone (ACTH) AVS, unilateral aldosterone overproduction was confirmed by a LI >2. In post-ACTH AVS, unilateral aldosterone overproduction was confirmed by a LI >4 ( 7 ). In total, 114 patients with PA underwent successful pre-ACTH AVS.…”
Section: Methodsmentioning
confidence: 95%
“…Further, all testing protocols adhered to the guidelines of the Japan Endocrine Society ( 6 ). The criterion for successful selective catheterization was the ratio of adrenal vein to inferior vena cava cortisol concentrations ( 7 ). The lateralization index (LI) is defined as the ipsilateral adrenal vein aldosterone to cortisol concentration ratio over the contralateral aldosterone to cortisol ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the adrenal glands of PA patients demonstrated that 40% to 50% of adrenals with APAs contained APCCs in the non-tumor portions of APA ( 30 , 31 ). Interestingly, in Kometani et al ( 32 ) study that found a 94% prevalence of APCCs in 16 adrenal tissue adjacent to the APA; the number and summed-area of APCCs in APAs were significantly higher in patients with discordant AVS results whose diagnosis changed to bilateral PA post-adrenocorticotropic hormone (ACTH) stimulation. The authors therefore proposed that APA patients with multiple APCCs might have similar adrenocortical pathological conditions in the contralateral adrenal gland.…”
Section: Physiological and Pathological Aspects Of Apccsmentioning
confidence: 99%
“…This assumption would explain their finding that in the pre-ACTH group having multiple APCCs, the post- to pre-ACTH plasma aldosterone concentrations (PACs) ratio was markedly higher on the non-dominant than the dominant side. Although the aldosterone responsiveness of APCCs towards ACTH has not been thoroughly described, it is conceivable that ACTH stimulation triggers the synthesis of aldosterone by APCCs in the contralateral adrenal gland, resulting in a decreased lateralization index ( 32 ). As RAAS is systemically suppressed in PA patients, these findings indicate that APCCs might play a role in autonomous aldosterone production ( 12 ).…”
Section: Physiological and Pathological Aspects Of Apccsmentioning
confidence: 99%